2012
DOI: 10.1093/imrn/rns198
|View full text |Cite
|
Sign up to set email alerts
|

Diophantine Approximation and Automorphic Spectrum

Abstract: The present paper establishes quantitative estimates on the rate of diophantine approximation in homogeneous varieties of semisimple algebraic groups. The estimates established generalize and improve previous ones, and are sharp in a number of cases. We show that the rate of diophantine approximation is controlled by the spectrum of the automorphic representation, and thus subject to the generalised Ramanujan conjectures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 36 publications
2
65
0
Order By: Relevance
“…Later a systematic study of this property for homogeneous varieties X was undertaken in [16], where in particular it has been shown that • every α ∈ S n is (1, 0, b)-Dirichlet in S n for any…”
Section: Proofs Of Theoremsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later a systematic study of this property for homogeneous varieties X was undertaken in [16], where in particular it has been shown that • every α ∈ S n is (1, 0, b)-Dirichlet in S n for any…”
Section: Proofs Of Theoremsmentioning
confidence: 99%
“…Previously Fukshansky [15] used a theorem of Hlawka [20] about approximations of real numbers by Pythagorean triples to establish Theorem 1.1 in the special case of S 1 , and showed that one can take C = 2 √ 2. In [33] a version of the above theorem was established for all n with φ 1 replaced by φ 1/2⌈log 2 (n+1)⌉ and with an explicit dependence of C on n. Later Ghosh, Gorodnik and Nevo [16] did the same with φ 1 replaced by φ 1 4 −ε for all n and with C dependent on α and ε (see §4.1 for a more precise statement of their results).…”
Section: Introductionmentioning
confidence: 97%
“…, p n , q) ∈ Z n+1 lying on a quadratic variety of the form x 2 1 ± · · · ± x 2 d − y 2 = 1 to their limit points (with respect to the projective distance) lying on the unit sphere S n ⊂ R n . For general manifolds admitting group actions, Ghosh, Gorodnik and Nevo [29] also consider related Diophantine problems involving approximation by rational points. The Khintchine type theory for curves in dimensions n > 2 is simply nonexistent.…”
Section: Diophantine Approximation On Manifoldsmentioning
confidence: 99%
“…Using the bounds (13) when n = 2, Ghosh, Gorodnik, and Nevo [51] showed that there exists 0 > 0, depending only on r and δ, such that for every ∈ (0, 0 ) one can find an S-integer point z ∈ X(O S ) satisfying ||x − z|| ∞ and H(z)…”
Section: 3mentioning
confidence: 99%